Datenkapitalismus – eine ökonomische Betrachtung - Tobias Kretschmer; Lukas Wiewiorra; Jan Krämer; Andreas Oehler; Matthias Horn; Justus Haucap; Stefan Klein; Joschka Hüllmann (Wirtschaftsdienst, 2018)
Im Datenkapitalismus sind neue Kommunikationsunternehmen entstanden, deren Angebot als 'umsonst' erscheint. Ihr Geschäftsmodell basiert darauf, dass die Nutzer (Kunden) ihre Daten preisgeben und dafür entweder ein nachgefragtes Gut (Kommunikation, Medien, Waren und Dienstleistungen) ohne oder für geringere monetäre Zahlungen erhalten. Wie die Unternehmen die Daten verwenden, wissen die Nutzer in der Regel nicht, auch der pekuniäre Wert ihrer Daten lässt sich nicht einfach ermitteln. Ganz wichtig sind also mehr Transparenz und Kontrolle. Die neue Datenschutz-Grundverordnung macht zwar Datenportabilität möglich und unterstützt damit den Wettbewerb innerhalb der EU, sie lässt sich aber in der Praxis schwer wirksam umsetzen. – – Companies aggregate, process and monetise data about consumers by leveraging actively shared information as well as the data they glean from tracking offl ine transactions. Data-driven business models come in two forms: Firms either use the personal data of users to tailor their own offerings to them, or they sell the data to others who use it for their own ends. These models have different implications for the protection of consumers. While they are typically reasonably well-informed about the data they transmit to a particular firm, they have less control about whom their data is sold on to. Consumers are regularly confronted with a lot of privacy-relevant information and choices, but they struggle to make decisions that are in line with their stated privacy preferences. Therefore, regulation should address privacy design concepts that actually foster control. The right to data portability is one of the fundamentally new elements of the General Data Protection Regulation. However, its economic implications are potentially very complex and, under certain circumstances, data portability may not even be in the interest of consumers. Nevertheless, the strengthening of consumer rights may likewise support competition. The monetary value of data is difficult to calculate. But if consumers are interested in a fair profit share of personal data markets, policy makers may disregard their claims. One article highlights the transformation in the academic publishing industry (STM) from a traditional focus on publishing services to a new emphasis on data analytics by reconstructing and illustrating the mechanisms of data capitalism. It offers an explanation for the growing profitability and concentration of the STM industry despite the growing open science movement.
Keywords: 330